Hyperspectral downward irradiance observed during cruise aboard RV IBIS on Lake Victoria, Uganda, from 13 to 15 October 2021 - Anthony Gidudu; Shungudzemwoyo Pascal Garaba; Lydia Letaru; Prince Natuwera; Ronald Semyalo; Robinah Kulabako; Justine Amulen; William Okello (PANGAEA, 2022)
Hyperspectral radiometric quantities were observed at a 5-minute sampling interval in the Ugandan portion of Lake Victoria during a scientific field campaign aboard research vessel (RV) IBIS from 13 to 15 October 2021. The three day fieldwork was cooridnated starting from the Napoleon Bay, Jinja, Uganda. A radiometer setup with one TriOS RAMSES-ACC hyperspectral cosine irradiance meter to measure incoming solar irradiance was installed using a custom-made frame at the bow of RV IBIS. Data logging of raw and calibrated radiometric quantities was automated using TriOS MSDA XE version 8.9.2 software. Further processing was done using Mathworks Matlab 2016a and R software. Processed data was interpolated to 1 nm spectral resolution using PCHIP function in Matlab between 320 and 950 nm. Only the data with valid GPS coordinates and with spectra contributing less than 3% is included in this file, the rest of the data is available on request.
In: Gidudu, A et al. (2022): Hyperspectral above-water radiometric quantities observed during cruise aboard RV IBIS on Lake Victoria, Uganda, from 13 to 15 October 2021 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.947714